SIMULATION ON ANHYDROUS ETHANOL PRODUCTION IN EXTRACTIVE DISTILLATION USING GLYCEROL WITH SPLIT-FEED CONFIGURATION - MD NADZRI, NOR NADIAH NADHIRAH (IRC, 2017)
Production of ethanol via fermentation process typically has high water content which is about 50-70 wt% of water that does not meet the industrial demand of anhydrous ethanol, which is maximum 0.05 wt% of water. Thus, separation of ethanol-water is vital due to its application in various ways in chemical industry. Production of anhydrous ethanol has been widely practiced in extractive distillation using a solvent due to its minimum boiling azeotrope formation. Typical solvent in extractive distillation, ethylene glycol has been reported to contribute in health problems due to its toxicity. Hence, in this study, glycerol, an environmental friendly solvent is selected to be the alternative motivated by its abundancy via biodiesel production. Also, it is important to highlight that ethanol dehydration is one of the major energy intensive systems in industry. Therefore, this study proposed to simulate the feed-splitting method, an energy saving technique in ethanol dehydration process. To achieve those objectives, Aspen HYSYS simulation software is used throughout this project to evaluate the performance of glycerol as the separating agent and also to analyse the energy efficiency between the new proposed configuration and the conventional process. Results obtained shows that glycerol has better performance as solvent, especially in terms of purity of ethanol in distillate (99.85 mol%), as compared to ethylene glycol (99.17 mol%). Plus, simulating glycerol as the solvent also reduced the energy consumption by more than 60%. Application of feed-splitting method using glycerol is proven to save the condenser duty by 71% and reboiler duty by 59% where this might contribute to petrochemical industries in their effort for cost optimization and energy efficient.